Use of levoglucosan, potassium, and water-soluble organic carbon to characterize the origins of biomass-burning aerosols - Urban, Roberta Cerasi; Lima-Souza, Michele [UNESP]; Caetano-Silva, Leticia [UNESP]; Queiroz, Maria Eugenia C.; Nogueira, Raquel F. P. [UNESP]; Allen, Andrew G. [UNESP]; Cardoso, Arnaldo A. [UNESP]; Held, Gerhard [UNESP]; Campos, Maria Lucia A. M. (Pergamon-Elsevier B.V. Ltd, 2012)
Three chemical species related to biomass burning, levoglucosan, potassium and water-soluble organic carbon (WSOC), were measured in aerosol samples collected in a rural area on the outskirts of the municipality of Ourinhos (São Paulo State, Brazil). This region is representative of the rural interior of the State, where the economy is based on agro-industrial production, and the most important crop is sugar cane. The manual harvesting process requires that the cane be first burned to remove excess foliage, leading to large emissions of particulate materials to the atmosphere. Most of the levoglucosan (68-89%) was present in small particles (<1.5 mu m), and its concentration in total aerosol ranged from 25 to 1186 ng m(-3). The highest values were found at night, when most of the biomass burning occurs. In contrast, WSOC showed no diurnal pattern, with an average concentration of 5.38 +/- 2.97 mu g m(-3) (n = 27). A significant linear correlation between levoglucosan and WSOC (r = 0.54; n = 26; p < 0.0001) confirmed that biomass burning was in fact an important source of WSOC in the study region. A moderate (but significant) linear correlation between levoglucosan and potassium concentrations (r = 0.62; n = 40; p < 0.0001) was indicative of the influence of other sources of potassium in the study region, such as soil resuspension and fertilizers. When only the fine particles (<1.5 pm; typical of biomass burning) were considered, the linear coefficient increased to 0.91 (n = 9). In this case, the average levoglucosan/K+ ratio was 0.24, which may be typical of biomass burning in the study region. This ratio is about 5 times lower than that previously found for Amazon aerosol collected during the day, when flaming combustion prevails. This suggests that the levoglucosan/K+ ratio may be especially helpful for characterization of the type of vegetation burned (such as crops or forest), when biomass-burning is the dominant source of potassium. The relatively high concentrations of WSOC (and inorganic ions) suggest an important influence on the formation of cloud condensation nuclei, which is likely to affect cloud formation and precipitation patterns. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Brazil; São Paulo State; Sugar cane; Cloud condensation nuclei; Organic carbon